Gene mutations differently impact the prognosis of the myelodysplastic and myeloproliferative classes of chronic myelomonocytic leukemia. Issue 6 (10th April 2014) - Cervera, Nathalie; Itzykson, Raphael; Coppin, Emilie; Prebet, Thomas; Murati, Anne; Legall, Stevan; Vey, Norbert; Solary, Eric; Birnbaum, Daniel; Gelsi‐Boyer, Véronique
<x xml:space="preserve">Abstract</x> Initially classified in the myelodysplastic syndromes (MDSs), chronic myelomonocytic leukemia (CMML) is currently considered as a MDS/myeloproliferative neoplasm. Two classes—myelodysplastic and myeloproliferative—have been distinguished upon the level of the white blood cell count (threshold 13 G/L). We analyzed mutations in 19 genes reported in CMML to determine if and how these mutations impacted the respective prognosis of the two classes. We defined four major mutated pathways (DNA methylation, ASXL1, splicing, and signaling) and determined their prognostic impact. The number of mutated pathways impacted overall survival in the myelodysplastic class but not in the myeloproliferative class. The myeloproliferative class had a worse prognosis than the myelodysplastic class and was impacted by RUNX1 mutations only. Our results argue for a reclassification of CMML based on the myelodysplastic/myeloproliferative status. Am. J. Hematol. 89:604–609, 2014. © 2014 Wiley Periodicals, Inc.